EXPLORE THE EFFICACY AND SAFETY OF ONCE-DAILY ORAL RIVAROXABAN FOR THE PREVENTION OF CARDIOVASCULAR EVENTS IN PATIENTS WITH NON- VALVULAR ATRIAL FIBRILLATION SCHEDULED FOR CARDIOVERSION (Неотложная медицинская помощь)
Cappato R., Ezekowitz M.D., Klein A.L., et al. Rivaroxaban vs. vitamin K antagonists for cardioversion in atrial fibrillation // Eur. heart J. – 2014. Sep. 2. [Epub ahead of print].